Sosialisasi Peningkatan Mutu Pelayanan dan Keselamatan Pasien di Klinik Dr. Sunedi Palembang - Herdiani, Rini; S, Sunirah; Mayangsari, Junawalia (Yayasan Daarul Huda Kruengmane, 2025)
Improving the quality of service is a top priority in all clinics. These efforts are carried out through the construction of facilities, infrastructure, procurement of equipment and personnel as well as other software, in line with the construction of clinic in general. In addition to improving the quality of services, the quality of human resources also needs to be improved. Human resources owned by clinic will also affect quality of health services, the limited diversity of types of health workers will result in hospital performance in achieving hospital service quality indicators. One of the obstacles to the efforts of clinic in providing satisfactory medical services at this time is the limited resources and supporting facilities, especially medical technology, which is a crucial point in medical treatment. Medical and other nursing personnel are also one of the main pillars for hospitals that can support the competitive advantage of clinic if the management system and human resource development in it can be managed properly, which includes fulfilling standardized competency indicators, developing expertise with trainings. and nursing care, objective performance appraisal, fair distribution of working hours, as well as a compensation system that can provide job satisfaction in order to improve individual performance which leads to an increase in overall clinic performance. In this case, there are still many hospital managements who do not understand the importance of the elements of service quality management and human resource management. Therefore, an understanding is needed clinic leaders about the importance of this for the process of improving the quality of service and the quality of performance will be a long-term investment owned.